HUBUNGAN TERPAAN MEDIA SOSIAL APLIKASI RUANGGURU TERHADAP MOTIVASI BELAJAR SISWA KELAS VI DI SD NEGERI 2 TAHUNAN - Della Putri, Kiki Shalsa; Sekar Wangi, Maya; Maserona Sarungu, Lukas (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
ABSTRACT This research aims to analyze the relationship between the impact of social media from the Ruangguru application and the learning motivation of sixth-grade students at SD Negeri 2 Tahunan. This study employs new media theory in examining the relationship between the impact of social media from the Ruangguru application and the learning motivation of sixth-grade students at SD Negeri 2 Tahunan. The type of research conducted is quantitative research, where data collection is carried out using questionnaires. The population and sample in this study consist of 30 sixth-grade students (respondents) from SD Negeri 2 Tahunan. The analysis technique used is Spearman's correlation. The results indicate that the variable of the impact of social media from the Ruangguru application has a significant simultaneous effect on the learning motivation of sixth-grade students at SD Negeri 2 Tahunan. The variable of the impact of social media from the Ruangguru application also has a significant partial effect on the learning motivation of sixth-grade students. The calculated t value is 4.310 with a p-value of 0.001<0.05, thus H1 is accepted. This indicates that there is a relationship provided by the Ruangguru Application (X) towards the dependent variable (Y) in sixth-grade students of SD Negeri 2 Tahunan. Keywords: Media exposure, Application, Ruangguru, learning motivation.